Packet Warriors: An Academic Mobile Action Game for Promoting OSI Model Concepts to Learners - Uiphanit, Thanakorn; Bhattarakosol, Pattarasinee; Suanpong, Kwanrat; Iamsupasit, Sompoch (International Journal of Interactive Mobile Technologies (iJIM), 2019)
This research aims to develop a game to teach the theoretical concepts of the OSI reference model to students who must learn data communication and networking as a compulsory or an elective subject. The survey was administered to most students at Suan Sunandha Rajabhat University by a questionnaire to assess a suitable game for students of this generation. The result showed that action games are the most popular game for them. Then, a script of the OSI reference model was drawn based on the theoretical contents and the software design and implementation were performed. After finishing this development process, 19 third-year undergraduate students majoring in information sciences at Suan Sunandha Rajabhat University tested this system. The evaluation process was performed using pretest and posttest data analyzed by a paired samples t-test at a 95% confidence level. The result of this study shows that the action game ‘Packet Warrior’ is an efficient tool to help students improve their learning capabilities via fun and good relationships with friends.